Bio-efficacy of imidacloprid and bifenthrin against mustard aphid (Lipaphis erysimi) on Brassica rapa subsp oleifera - DEVEE, ANJUMONI; BARUAH, A A L H (The Indian Journal of Agricultural Sciences, 2012)
The efficacy, relative toxicity, residual toxicity and dissipation behaviour of imidacloprid and bifenthrin were evaluated against mustard aphid [Lipaphis erysimi (Kalt.)] during 2006-07 and 2007-08. Imidacloprid (RiBo 17.8 SL @ 20, 40 and 60 g ai/ha), bifenthrin (Marker 20 per cent EC @ 60, 80 and 100 g ai/ha) and deltamethrin (as standard check) (Decis 2.8 per cent EC @ 15 g ai/ha) were evaluated against mustard aphid, Lipaphis erysimi (Kalt.) and was found effective in reducing the aphid population in comparision to control. The highest mortality of aphids and marketable yield was registered by imidacloprid @ 60 g ai/ha, while highest cost benefit ratio was found in imidacloprid @ 20 g ai/ha and proved sufficient to optimize the yield. The LC50 values were 0.00017 and 0.00015 for imidacloprid, 0.00152 and 0.00122 for bifenthrin, 0.00199 and 0.00134 for deltamethrin, after 24 and 48 hr of treatment, respectively. Imidacloprid was 8.93 times and bifenthrin 1.10 times more toxic than deltamethrin after 48 hr of treatment. For evaluation of persistence and residual toxicity of imidacloprid the mortality data were taken up to 48 hr, within different exposure periods of 1, 3, 5, 10 and 15 days after application of insecticides. Based on the index of persistence toxicity, the order of effectiveness for the L. erysimi were imidacloprid @ 60 g a.i/ha (1014.23)> imidacloprid @ 40 g a.i/ha (931.37) > imidacloprid @ 20 g a.i/ha (820.41)> deltamethrin 15 g a.i/ha (707.93)> bifenthrin @ 100 g a.i/ha (659.76)> bifenthrin @ 80 g a.i/ha (611.12)>bifenthrin @ 60g a.i/ha (545.25). The dissipation behaviour of imidacloprid under field condition on Brassica rapa L. subsp. oleifera (toria) crop was studied in tender shoots and seeds. The initial deposits of imidacloprid @ 20, 40 and 60 g a.i /ha were 0.830, 1.126 and 1.280, respectively. Imidacloprid residues reached below its detectable level after 5th and 10th day of its application at lower and higher rates. The half life values were 1.44, 1.96, 1.67 days for imidacloprid @ 20, 40 and 60 g a.i/ha, respectively. Based on the observations, a waiting period of at least four days after imidacloprid application @ 20 g a.i/ha is considered safe from point of health hazards due to toxic effect of residues in leaves.